Bone-by-bone: A detailed skull description of the White-headed dwarf gecko Lygodactylus picturatus (Peters, 1870). Issue 2 (10th December 2021) - Lobon-Rovira, Javier; Bauer, Aaron
ABSTRACT: The Lygodactylus genus is one of the most species-rich genera of gekkonid lizards in Africa. It is one of relatively few exclusively diurnal geckos' lineages and its members include some of the smallest gekkonids. Osteological features within Lygodactylus have never been addressed in detail. We here provide a detailed bone-by-bone skull description of Lygodactylus picturatus to expand the knowledgebase on gecko cranial structure. High-Resolution X-ray Computed Tomography (HRCT) has been used, followed by bone-by-bone segmentation and description. As expected, L. picturatus presents some modifications on the basic gekkotan plan due to miniaturisation, such as an increase in the overlap area of the muzzle unit and lost or reduction of jugal bone. In addition, the skull of this species is characterised by the absence of the squamosal, fused nasals, reduced postorbitofrontal bone and extremely rounded parietal bones. Finally, we observed a reduction of the orbital space, in comparison with other miniaturised gekkotans, presumably as a consequence of their diurnal behaviour and niche preference.